The experiences of sonographers with regard to report writing and communicating their findings - Cassandra A. Ferreira; Barbara van Dyk; Padidi L. Mokoena (AOSIS, 2022)
Background: Sonographers in South Africa are legally allowed to write their own reports; however, they often lack adequate training in providing a well-structured and coherent formal written report. Aim: The aim of this study was to explore and describe how sonographers in the Gauteng province experience the responsibility of report writing and to develop recommendations that could assist sonographers in the execution of their duty. Setting: Focus group discussions (FGDs) with sonographers from private and public hospitals located in Gauteng province were conducted at neutral locations that were convenient for the sonographers. Methods: A qualitative phenomenological research design was used for this study. A two-stage sampling approach was employed to recruit information-rich sonographers to partake in this study. Purposeful sampling was used to select sonographers based on their first-hand experience of report writing, followed by snowball sampling which allowed the researcher access to new participants on the recommendation of previous sonographers. Thirteen female sonographers voluntarily participated in the study, and the FGDs continued until data saturation was reached. The views and opinions of the sonographers were analysed using content analysis. Results: Key findings of this study indicated that sonographers felt unprepared to describe ultrasound findings correctly in order to provide a coherent and well-structured formal written report. Conclusion: Sonographers suggested the use of workshops or further training at higher educational institutions (HEIs) to support sonographers in their report-writing role. Contribution: The experiences identified by sonographers can assist HEIs to provide further training or workshops to support sonographers in communicating their findings effectively.